Research Methods for Studying Groups and Teams: A Guide to Approaches, Tools, and Technologies, 1st edition - Hollingshead, Andrea, editor (Routledge, 2020)
This volume provides an overview of the methodological issues and challenges inherent in the study of small groups from the perspective of seasoned researchers in communication, psychology and other fields in the behavioral and social sciences. It summarizes the current state of group methods in a format that is readable, insightful, and useful for both new and experienced group researchers. This collection of essays will inspire new and established researchers alike to look beyond their current methodological approaches, covering both traditional and new methods for studying groups and exploring the full range of groups in face-to-face and online settings.